2009
DOI: 10.1200/jco.2008.19.5750
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sentinel Lymph Node Biopsy Alone and Completion Axillary Lymph Node Dissection for Node-Positive Breast Cancer

Abstract: Compared with SLNB alone, completion ALND does not appear to improve outcomes for breast cancer patients with microscopic nodal metastases; however, there was a nonsignificant trend toward better outcomes with completion ALND for those with macroscopic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
208
0
8

Year Published

2010
2010
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 321 publications
(233 citation statements)
references
References 33 publications
13
208
0
8
Order By: Relevance
“…The risk of further nonsentinel lymph node involvement was reported to be approximately 15% to 20% in patients with sentinel lymph node micrometastasis detected by histological examination [25][26][27][28][29] ; however, it remains controversial whether completion axillary lymph node dissection is needed for patients with sentinel lymph node micrometastasis [30][31][32][33][34] or micrometastasis has a prognostic impact. 2,19,21,35,36 One of the reasons for these controversies is that the conventional histopathological examination is not standardized, and its ability to measure accurate total metastatic volume in a lymph node, particularly for low-volume metastases, is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of further nonsentinel lymph node involvement was reported to be approximately 15% to 20% in patients with sentinel lymph node micrometastasis detected by histological examination [25][26][27][28][29] ; however, it remains controversial whether completion axillary lymph node dissection is needed for patients with sentinel lymph node micrometastasis [30][31][32][33][34] or micrometastasis has a prognostic impact. 2,19,21,35,36 One of the reasons for these controversies is that the conventional histopathological examination is not standardized, and its ability to measure accurate total metastatic volume in a lymph node, particularly for low-volume metastases, is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive lobular 4 (13) 21 (13) 13 (20) 6 (15) 5 (25) Select studies of patients with positive SLN and who did not undergo ALND have demonstrated low regional recurrence rates in the setting of adjuvant systemic therapy and RT (Table 5). 1,[5][6][7][8][9][10][11][12][13][14]28 Those series differed with respect to the length of median follow-up, the definition of a positive SLN, reasons for omitting ALND, and the receipt of systemic therapy. Although several of those reports 1,5,7,11 described the RT fields used, none reported treatment outcomes stratified by RT field design.…”
Section: Discussionmentioning
confidence: 99%
“…Methods of enhanced pathologic assessment of the SLN node have resulted in the increased detection of small-volume (micrometastases and isolated tumor cells) SLN metastases. 1,2 Nomograms that identify patients at low risk for additional lymph node metastases have guided the selection of patients for SLNB alone, 3 leading to a nationwide decline in the performance of completion axillary dissection (cALND). 1 These trends are reflected at our own institution, where cALND rates between 1998 to 2008 decreased from 85% to 73%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations